Presenting the COGNIFOG Framework: Architecture, Building Blocks and Road toward Cognitive Connectivity - Adame, Toni; Amri, Emna; Antonopoulos, Grigoris; Azaiez, Selma; Berne, Alexandre; Camargo, Juan Sebastian; Kakoulidis, Harry; Kleisarchaki, Sofia; Llamedo, Alberto; Prasinos, Marios; Psara, Kyriaki; Shumaiev, Klym (Sensors (Basel, Switzerland), 2024)
In the era of ubiquitous computing, the challenges imposed by the increasing demand for real-time data processing, security, and energy efficiency call for innovative solutions. The emergence of fog computing has provided a promising paradigm to address these challenges by bringing computational resources closer to data sources. Despite its advantages, the fog computing characteristics pose challenges in heterogeneous environments in terms of resource allocation and management, provisioning, security, and connectivity, among others. This paper introduces COGNIFOG, a novel cognitive fog framework currently under development, which was designed to leverage intelligent, decentralized decision-making processes, machine learning algorithms, and distributed computing principles to enable the autonomous operation, adaptability, and scalability across the IoT–edge–cloud continuum. By integrating cognitive capabilities, COGNIFOG is expected to increase the efficiency and reliability of next-generation computing environments, potentially providing a seamless bridge between the physical and digital worlds. Preliminary experimental results with a limited set of connectivity-related COGNIFOG building blocks show promising improvements in network resource utilization in a real-world-based IoT scenario. Overall, this work paves the way for further developments on the framework, which are aimed at making it more intelligent, resilient, and aligned with the ever-evolving demands of next-generation computing environments.